Émile Ollivier’s Exiles - Kyloušek, Petr (Oltreoceano - Rivista sulle migrazioni, 2024)
Migrant literature represents an important stage in the dynamics of Quebec literature, both scripturally and theoretically. The article first summarizes the structuring axiological elements of the Quebec literary field that, from the 1960s onwards, paved the way for the entry and integration of migrant authors into the Quebec canon. These include identity and cultural territorialization, felt to be incomplete by both Quebec authors (Jacques Ferron) and critics (Laurent Mailhot), and which Pierre Nepveu likens to migrant authors, emphasizing the similarities. The complimentary component of the process belongs to the Italo-Québécois and Haitians who, in the 1990s, thematized and theorized the exilic situation, transforming the perception of cultural and ethnic otherness into an existential, ethical and scriptural problematic translated by the concepts of nomadism and enracinerrance. Unlike his fellow exiles - Robert Berrouët-Oriol, Jean Claude Charles, Joël Des Rosiers - Émile Ollivier treats the exilic condition on two complementary levels. The first considers the nomadic-sedentary relationship from a historical perspective, noting the axiological overturn in favor of nomadism as the dominant human status in the postmodern world. The second deduces the philosophical consequences associated with writing. The discussion is illustrated by three works - the theoretical reflection Repérages (2001) and the two novels from the latest period Passages (1994) and La Brûlerie (2004). The analysis reveals the link between the exilic theme and the consequences Émile Ollivier draws from it for the structuring of spatiality, narration and the status of writing as a manifestation of the dynamics of the void. As an example of an integrating process, Émile Ollivier's poetics anticipates certain post-2000 trends in Quebec literature.